Conditions of Agricultural Growth in Developing Countries (Invited Lecture) (The Pakistan Development Review, 1988)
Economic development is hardly possible without an increase in agricultural production. This holds especially true for the development of industry and other non-agricultural sectors. How else should a rapidly increasing population outside the agricultural sector be maintained with necessary agricultural goods? Though this is a simple truth agricultural production, especially food production increase has been far from satisfactory in many developing countries. Between 1974-76 and 1982-84 per capita food production in industrialized countries increased at a much higher rate than in developing countries and in almost 50 developing countries it has even declined during the same period. 1 Many developing countries are now heavily dependent on food imports to sustain their urban population, though they have comparative advantages to produce agricultural products. How is this defect to be explained? Technical reasons are not prevailing. Though only in Africa and South America unused arable land is available to a large extent but not in Asia, it would be possible to dramatically increase agricultural production by introducing new seed varieties, chemical fertilizer and irrigation. The main factors to hamper agricultural growth are political, social and economic. T. H. Schultz wrote in 1978: "What is needed are many Green Revolutions that would increase agricultural production throughout low income countries. They could be had, but they are presently suppressed by the lack of adequate incentives."2 In many developing countries the farm sector is exploited by the urban sector and a stream of agricultural surplus is channelled out of the farm sector to feed the nonagricultural population. Very often the prices of farm products are artificially held down.